2021
DOI: 10.1177/08901171211056584
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Healthy Food Access and Nutrition in Primary Care: A Systematic Scoping Review of Food Prescription Programs

Abstract: Objective To conduct a scoping review to synthesize evidence on food prescription programs. Data Source A systematic search of PubMed, CINAHL, Web of Science, Embase, and the Cochrane Library was conducted using key words related to setting, interventions, and outcomes. Study Inclusion and Exclusion Criteria Publications were eligible if they reported food prescription administered by a health care practitioner (HCP) with the explicit aim of improving healthy food access and consumption, food security (FS), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 56 publications
(275 reference statements)
2
43
0
Order By: Relevance
“…Produce prescription programs have been implemented in primary care settings to address FI and diet quality and many targeting adults have been evaluated for feasibility and impact [ 25 , 26 ]. Few programs specifically addressing families with young children have been evaluated and all, except one [ 27 ], have used a client-choice, external-to-the-home model of providing supplemental produce resources (e.g., farmer’s market or food pantry vouchers) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Produce prescription programs have been implemented in primary care settings to address FI and diet quality and many targeting adults have been evaluated for feasibility and impact [ 25 , 26 ]. Few programs specifically addressing families with young children have been evaluated and all, except one [ 27 ], have used a client-choice, external-to-the-home model of providing supplemental produce resources (e.g., farmer’s market or food pantry vouchers) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…This aligns with findings from Trapl, et al [6] who found daily fruit intake increased from an average of 1.6 servings to 2.4 servings, and daily vegetable intake increased from 1.7 to 2.5 servings, comparing preto post-intervention. In a scoping review [13], it was found that although food prescriptions can improve FV intake and reduce food insecurity, there is a need for more rigorous studies, with larger sample sizes, control groups, and validated measures of diet, food security, and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Bryce and colleagues [9] found that the fresh Rx program in Detroit resulted in a statistically significant decrease in HbA 1 C but no changes in blood pressure (BP) or BMI. Ferrer, et al [5], Veldheer, et al [10], and Haddad-Lacle, et al [12] all found reductions in HbA 1 C. Overall, in a scoping review of 23 food prescription programs, Little et al [13] found that food prescriptions can improve FV intake and reduce food insecurity, but there was limited and mixed evidence for impacts on diet-related health outcomes (BP, weight, BMI, HbA1c) [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence surrounding the impacts of produce prescription programs is still being researched, with 85% of produce prescription studies having been published over the last 4 years (12). Participant input is integral to help guide future interventions that address social needs, and there is a need for qualitative studies that capture participant feedback on how they were impacted by social programs, such as food prescription programs, during the pandemic [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%